LRRK2 N551K and R1398H variants are protective in Malays and Chinese in Malaysia: A case–control association study for Parkinson's disease. Issue 11 (5th September 2019) - Gopalai, Aroma Agape; Lim, Jia Lun; Li, Hui‐Hua; Zhao, Yi; Lim, Thien Thien; Eow, Gaik B.; Puvanarajah, Santhi; Viswanathan, Shanthi; Norlinah, Mohamed Ibrahim; Abdul Aziz, Zariah; Lim, Soo Kun; Tan, Chong Tin; et al.
Abstract: Background: The LRRK2 gene is associated with Parkinson's disease (PD) as a number of mutations within the gene have been shown to be susceptibility factors. Studies on various global populations have determined that mutations such as G2019S, G2385R, and R1628P in LRRK2 increase the risk of developing PD while the N551K‐R1398H haplotype is associated with conferring protection against developing PD. Here we report a study looking at the N551K and R1398H variants for the first time in the Malaysian population. Methods: Cases (523) which conformed to the United Kingdom PD Brain Bank Criteria for PD were recruited through trained neurologists and age‐ and ethnically matched controls (491) were individuals free of any neurological disorder. The N551K and R1398H mutations were genotyped using the Taqman SNP genotyping assay. Results: A significant protective association for N551K was found in those of Malay ancestry, with a protective trend seen for R1398H. A meta‐analysis of Chinese individuals in this cohort with other published cohorts of Chinese ancestry indicated a significant protective role for N551K and R1398H. Conclusion: This study reports that the N551K‐R1398H haplotype is also relevant to the Malaysian population, with a significant protective effect found in those of Malay and Chinese ancestries. Abstract : Variants in the LRRK2 gene, N551K and R1398H have a significant protective association Malays and Chinese in a case–control study on Parkinson's Disease in Malaysia.